Bornyl caffeate induces apoptosis in human breast cancer MCF-7 cells via the ROS- and JNK-mediated pathways - Yang Chuan-bin; Pei Wei-jing; Zhao Jia; Cheng Yuan-yuan; Zheng Xiao-hui; Rong Jian-hui (Acta Pharmacologica Sinica, 2016)
Chuan-bin YANG1, Wei-jing PEI2, Jia ZHAO1, Yuan-yuan CHENG1, Xiao-hui ZHENG2, 3, Jian-hui RONG1, * 1School of Chinese Medicine, Li Ka Shing Faculty of Medicine, The University of Hong Kong, Pokfulam, Hong Kong, China; 2RITS and NWU Joint Laboratory for New Drugs Research of TCM, Research Institute of Tsinghua University in Shenzhen, Shenzhen 518000, China; 3Key Laboratory of Resource Biology and Biotechnology in Western China, School of Life Sciences, Northwest University, Xi’an 710069, China Aim: To investigate the effects of bornyl caffeate discovered in several species of plant on human breast cancer cells in vitro and the underlying mechanisms. Methods: Human breast cancer cell line MCF-7 and other tumor cell lines (T47D, HepG2, HeLa, and PC12) were tested. Cell viability was determined using MTT assay, and apoptosis was defined by monitoring the morphology of the nuclei and staining with Annexin V-FITC. Mitochondrial membrane potential (MMP) was measured using JC-1 under fluorescence microscopy. Intracellular reactive oxygen species (ROS) were assessed by flow cytometry. The expression of apoptosis-associated proteins was determined by Western blotting analysis. Results: Bornyl caffeate (10, 25, and 50 µmol/L) suppressed the viability of MCF-7 cells in dose- and time-dependent manners, but neither caffeic acid nor borneol showed cytotoxicity at a concentration of 50 μmol/L. Bornyl caffeate also exerted cytotoxicity to HepG2, Hela, T47D, and PC12 cells. Bornyl caffeate dose-dependently induced apoptosis of MCF-7 cells, increased the expression of Bax and decreased the expression of Bcl-xl, resulting in the disruption of MMP and subsequent activation of caspase-3. Moreover, bornyl caffeate triggered the formation of ROS and activated p38 and c-Jun JNK. In MCF-7 cells, the cytotoxicity of bornyl caffeate was significantly attenuated by SB203580 (p38 inhibitor), SP600125 (JNK inhibitor), z-VAD (pan-caspase inhibitor) or the thiol antioxidant L-NAC. Conclusion: Bornyl caffeate exerts non-selective cytotoxicity against cancer cells of different origin in vitro. The compound induces apoptosis in human breast cancer MCF-7 cells via the ROS- and JNK-mediated pathways. Keywords: bornyl caffeate; anticancer drug; human breast cancer; T47D; HepG2; HeLa; PC12; apoptosis; caspase-3; ROS; p38; JNK This work was supported by the Seed Funding Programme for Basic Research, University of Hong Kong (Project 201111159212, to JR) and the National Natural Science Foundation of China, Specialized Research Fund for the Doctoral Program of Higher Education on 2011 (project 20106101110001, to XZ). * To whom correspondence should be addressed. E-mail jrong@hkucc.hku.hk Received 2013-08-13 Accepted 2013-09-29